LANGUAGE GAMES IN LITERARY TEXTS REVIEW OF DISCUSSION THE LANGUAGE GAMES IN LITERARY TEXTS - Shaxnoza Sagatova (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The article considers about the analysis and a clear definition of the term language game and the study of this phenomenon in scientific works. There were found and systematized the content of the concept of a language game in the studies of domestic and foreign scientists. This work consists of several parts. First, the idea of ??language games is described, how it originated and what its essence is. Then the language game is viewed in the light of metalinguistics and communication theory. After that, the language game is understood as a lexico-stylistic device and is considered as a linguistic experiment. Finally, the functions of the language gamesare described. Language games are a kind of analytical method (set of techniques) to clarify the language. Language games are understood as models (samples, types) of the language, and its variable functions. From the point of view of compliance with speech realities, language games can be interpreted as local areas or aspects of language, as integral languages ??of a simpler type than a complex modern language, or as the practice of teaching children their native language. Being simplified speech forms, language games actually underlie the complicated forms and therefore serve as a convenient abstraction that provides a key to understanding them. Language games are thought of as components of activities or forms of life, moreover, no less diverse than the life practices themselves. In different situations, people do this or that, as a rule, combining object and other actions with speech.